Elevated extracellular CO2 level affects the adaptive transcriptional response and survival of human peripheral blood mononuclear cells toward hypoxia and oxidative stress (Medical Journal of Indonesia, 2021)
BACKGROUND High carbon dioxide (CO2) level from indoor environments, such as classrooms and offices, might cause sick building syndrome. Excessive indoor CO2 level increases CO2 level in the blood, and over-accumulation of CO2 induces an adaptive response that requires modulation of gene expression. This study aimed to investigate the adaptive transcriptional response toward hypoxia and oxidative stress in human peripheral blood mononuclear cells (PBMCs) exposed to elevated CO2 level in vitro and its association with cell viability. METHODS PBMCs were treated in 5% CO2 and 15% CO2, representatives a high CO₂ level condition for 24 and 48 hours. Extracellular pH (pHe) was measured with a pH meter. The levels of reactive oxygen species were determined by measuring superoxide and hydrogen peroxide with dihydroethidium and dichlorofluorescin-diacetate assay. The mRNA expression levels of hypoxia-inducible factor (HIF)-1α, HIF-2α, nuclear factor (NF)-κB, and manganese superoxide dismutase (MnSOD) were analyzed using a real-time reverse transcriptase-polymerase chain reaction (qRT-PCR). Cell survival was determined by measuring cell viability. RESULTS pHe increased in 24 hours after 15% CO₂ treatment, and then decreased in 48 hours. Superoxide and hydrogen peroxide levels increased after the 24- and 48-hour of high CO₂ level condition. The expression levels of NF-κB, MnSOD, HIF-1α, and HIF-2α decreased in 24 hours and increased in 48 hours. The increased antioxidant mRNA expression in 48 hours showed that the PBMCs were responsive under high CO2 conditions. Elevated CO2 suppressed cell viability significantly in 48 hours. CONCLUSIONS After 48 hours of high CO₂ level condition, PBMCs showed an upregulation in genes related to hypoxia and oxidative stress to overcome the effects of CO2 elevation.